Mediale Entwürfe des Selbst Audiovisuelle Selbstdokumentation als Phänomen und Praktik der sozialen Medien - Dörre, Robert (Büchner-Verlag, 2022)
In recent years, new forms of public self-documentation have become popular on social media platforms and especially through so-called influencers, forming their own media cultural microcosm. Even though YouTube has become emblematic of this cultural technique, media self-documentations are also formative for other services such as Instagram, TikTok, or Snapchat. Robert Dörre understands the emergence of these self-designs as an aesthetic practice and traces the media-historical shifts that public self-documentation has experienced on the Internet. In order to make these specific aesthetics, rituals, motifs, and economies accessible to media cultural studies, the work approaches the phenomenon from five perspectives: The reception as authentic self, the self as part of social media, the self as brand, the serial self, and the self as amateur and artist.